EMPOWERING WOMEN’S ORGANIZATIONS FOR ANEMIA PREVENTION AND CONTROL IN TRIMURTI VILLAGE, SRANDAKAN SUB-DISTRICT, BANTUL, YOGYAKARTA, INDONESIA - Waryana Waryana; Supadi Supadi; Wiworo Haryani (Belitung Nursing Journal, 2016)
Background: Anemia in Indonesia is mostly caused by micronutrient deficiency such as iron. Although much have been done to address anemia in the community, the problem remains. As health is not solely government’s responsibility, community participation should be seen as an alternative effective approach. Objective: The influence of women’s organizations to community participation and their self-sustenance in anemia prevention and control was examined. Methods: It was a quasi-experimental study with pretest and post-test control group design involving 30 women in reproductive-age who were selected through a multi-stage random sampling method; and 20 health providers, of whom were members of Dasa Wisma, posyandu cadres, PKK, and Karang Taruna. At the intervention group, women’s organization in anemia prevention and control was enabled in order to increase community participation. Hemoglobin level was measured as the outcome of the intervention program. Results: By empowering women’s organization, participation level of community members in the intervention group significantly increased, shown by family’s willingness to provide and consume iron-sufficient foods in their daily diets. As an outcome, hemoglobin level of reproductive-aged women at the intervention group slightly raised from its initial level, whilst the level in the control group was relatively stagnant. Conclusion: Involving the community member has been proven as an effective approach in anemia prevention and control. Given that women’s social movement are existed in many settings, therefore, empowering such organization as a manifestation of community participation can be applied in other setting, and also for other health program.